Intraoperative imaging - Pamir, M. Necmettin; Seifert, Volker; Kiris, Talat (Acta neurochirurgica. Supplement, 2011)
Intraoperative imaging technologies have taken an ever-increasing role in the daily practice of neurosurgeons and the increasing attention and interest necessitated international interaction and collaboration. The Intraoperative Imaging Society was formed in 2007. This book brings together highlights from the second meeting of the Intraoperative Imaging Society, which took place in Istanbul-Turkey from June 14 to 17, 2009. Included within the contents of the book is an overview of the emergence and development of the intraoperative imaging technology as well as a glimpse on where the technology is heading. This is followed by in detail coverage of intraoperative MRI technology and sections on intraoperative CT and ultrasonography. There are also sections on multimodality integration, intraoperative robotics and other intraoperative technologies. We believe that this book will provide an up-to date and comprehensive general overview of the current intraoperative imaging technology as well as detailed discussions on individual techniques and clinical results.